Evaluation of the Effect of Different Remineralizing Agents and Ozone Application on Artificial Carises - ALKAN, ELİF; TAĞTEKİN, DİLEK (My University, 2024)
This study aimed to assess the combined and individual effects of different remineralization agents and ozone application on initial caries. Seventy-two premolar teeth were collected. Three different toothpastes (Ipana, ROCS, and Gumgumix) were utilized. The samples were divided into eight groups (n = 8) for experimentation (Distilled water, Ipana+Ozone, Gumgumix+Ozone, ROCS +Ozone, Ipana, Gumgumix, ROCS, Ozone). Microhardness measurements were conducted initially. All samples were then immersed in a demineralization solution for 72 hours to induce initial caries. Then, microhardness measurements were repeated, and pH cycles were carried out for one-week. Finally, microhardness measurements and SEM-EDS analyses were performed. Ipana+Ozone exhibited the highest microhardness value, which was statistically significant compared to other groups except ROCS+Ozone (p < 0.05). Distilled water, Gumgumix+Ozone, and Gumgumix displayed the lowest microhardness values. Ozone application with remineralization agents led to higher precipitation of Ca ions. The demineralized group showed the lowest Ca, P, and F ions. While Ipana +Ozone and ROCS+Ozone had the highest Ca ions, Gumgumix+Ozone had the highest P ions. Within the study’s limitations, it can be concluded that ozone gas positively impacts the remineralization process in initial caries lesions. Additionally, mineral-containing products demonstrated a noteworthy capacity to reverse the demineralization process.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ÇEVRE; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ENVIRONMENTAL; Çevre Mühendisliği; Fizik Bilimleri; Çevre Kimyası; Environmental Engineering; Physical Sciences; Environmental Chemistry; Initial Caries; Ozone; remineralization; ROCS Mineral Gel